2006
DOI: 10.1016/j.nutres.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic perspectives on the combination of α-lipoic acid and vitamin E

Abstract: Alpha-lipoic acid and vitamin E have synergistic effects, as determined in models of oxidant radical lesions. This review summarizes recent findings showing that the combination of alpha-lipoic acid plus vitamin E has beneficial effects in reducing oxidative damage in ischemic or other oxidationrelated pathological events. Both antioxidants are common in the normal human diet and side effects are very rare. Therefore, alpha-lipoic acid and vitamin E can counteract oxidative processes and could have an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…Alpha‐lipoic acid has the ability to be absorbed in the intestine and also can cross the blood–brain barrier. Therefore, its supplementation can impart hypotriglyceridemic and hypoglycemic properties in chicken birds along with other therapeutic benefits including stress management (Gonzalez‐Perez & Gonzalez‐Castaneda, ). However, the in vivo ALA and DHLA concentration remain indecisive until now.…”
Section: Action Mechanism Of α‐Lipoic Acidmentioning
confidence: 99%
“…Alpha‐lipoic acid has the ability to be absorbed in the intestine and also can cross the blood–brain barrier. Therefore, its supplementation can impart hypotriglyceridemic and hypoglycemic properties in chicken birds along with other therapeutic benefits including stress management (Gonzalez‐Perez & Gonzalez‐Castaneda, ). However, the in vivo ALA and DHLA concentration remain indecisive until now.…”
Section: Action Mechanism Of α‐Lipoic Acidmentioning
confidence: 99%
“…The α-LA can be synthesized de novo in most animals, plants and microorganisms and it is a cofactor of different complexes in the oxidative decarboxylation enzyme of the Krebs cycle, i.e., pyruvate dehydrogenase and α-ketoglutarate dehydrogenase (Bast and Haenen, 2003;Trattner et al, 2007). Previous studies have shown that α-LA and its reduced form as dihydrolipoic acid (DHLA) have potent antioxidant capacity in both aqueous and lipidic environments because of the amphiphilic property to cross the cell membrane and the blood brain barrier (Gonzalez-Perez and Gonzalez-Castaneda, 2006;Yoshikawa et al, 1996). Appropriate supplementation of α-LA in the diet can significantly improve growth performance, survival and antioxidant status in abalone Haliotis discus hannai (Zhang et al, 2010) and hybrid tilapia Oreochromis niloticus × Oreochromis aureus (Xiong et al, 2012) due to its ability to reduce reactive oxygen species (ROS) (Bast and Haenen, 2003) and regenerate other antioxidants such as vitamin C, vitamin E, glutathione, coenzyme Q10 and ubiquinone (Han et al, 1997;Park et al, 2006;Trattner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid (AA) (11) and α-lipoic acid (ALA) (5) are primary antioxidants in biological systems and are capable of breaking the chain of lipid peroxidation in cell membranes.…”
Section: Introductionmentioning
confidence: 99%